2012
DOI: 10.1111/j.1438-8677.2012.00633.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered allocation to roots and shoots in the endophyte‐infected seedlings of Puccinellia distans (Poaceae)

Abstract: Endophytes play an important role in ecological and evolutionary processes in plants and have marked economic value. Seed-transmitted fungal endophytes are conventionally regarded as mutualistic symbionts, but their fitness consequences for the offspring of the host are not clear. Puccinellia distans infected with the fungus Epichloë typhina (E+) produces seeds that are several times smaller than normal (E-). This observation suggests that the E+ seedlings face a developmental disadvantage. Our growth chamber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…E. typhina has been recorded in five populations of P. distans, with all growing in anthropogenic habitats (Lembicz and Olejniczak 2009). The association between E. typhina and P. distans has already been investigated in several studies (Czarnoleski et al 2013;Górzyńska et al 2011Górzyńska et al , 2017Lembicz et al 2011Lembicz et al , 2013Olejniczak and Lembicz 2007); we reported a previously unrecorded hyperparasite appearing as dark green spots on E. typhina stromata in 2010 (M. Lembicz and K. Górzyńska, annual report, unpublished).…”
Section: Methodsmentioning
confidence: 67%
“…E. typhina has been recorded in five populations of P. distans, with all growing in anthropogenic habitats (Lembicz and Olejniczak 2009). The association between E. typhina and P. distans has already been investigated in several studies (Czarnoleski et al 2013;Górzyńska et al 2011Górzyńska et al , 2017Lembicz et al 2011Lembicz et al , 2013Olejniczak and Lembicz 2007); we reported a previously unrecorded hyperparasite appearing as dark green spots on E. typhina stromata in 2010 (M. Lembicz and K. Górzyńska, annual report, unpublished).…”
Section: Methodsmentioning
confidence: 67%
“…Fungal endophytes that are horizontally transmitted and non-Clavicipitaceous (hereafter 'endophytes') reside within the tissues of nearly all terrestrial plants and can mediate plant stress tolerance via effects on plant physiology and gene expression (Arnold & Engelbrecht, 2007;Rodriguez et al, 2009;Czarnoleski et al, 2012;Torres et al, 2012). However, endophytic fungi can range from antagonistic to mutually beneficial (Carroll, 1988), making the development of a predictive framework for symbiont outcomes key to both a basic understanding and potential applications of endophytic fungi.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many of the classical well‐documented endophytes in the Clavicipitaceae also wholly or partially sterilize their hosts by producing their fruiting body (stroma) on the inflorescence (Bradshaw, ; Clay and Leuchtmann, ; Schardl et al., ). Many of these endophytes are seed‐transmitted, and experiments with “cured” and uncured seeds have shown effects on seedling growth and survival (Faeth and Hamilton, ; Gibert and Hazard, ), as well as on root/shoot ratios (Czarnoleski et al., ). Correspondingly, it is increasingly recognized that many endophytes are simply the nonfruiting hyphal stage of fungi that under other conditions or at other life stages may have overt pathogenic effects (Slippers and Wingfield, ; Newton et al., ; Junker et al., ).…”
Section: Discussionmentioning
confidence: 99%